Early Retirement Policy of Power Plant In Pelabuhan Ratu: A Multi-Level Governance Analysis To Support The Energy Transition In Indonesia - S. Silviana; Nanik Trihastuti; Sayyid Qutub Guntur Darsanto (Asian Journal of Social and Humanities, 2025)
The early retirement policy of the Pelabuhan Ratu Steam Power Plant (PLTU) with a capacity of 3x350 MW is one of the strategic steps in supporting Indonesia's energy transition towards a low-carbon energy system. This research uses a multi-level governance framework to analyze the roles of various actors, levels of government, and relationships between stakeholders in the formulation of this policy. With a qualitative method approach, this research combines bibliometric analysis to map the development of global literature related to early retirement PLTU and comparative case studies of similar policies in other countries. The results identify key challenges, such as regulation, financing, and governance transparency, as well as key success factors, including community engagement and international support. The study also examines the impact of policy implementation on power sector decarbonization, air quality, and greenhouse gas emission reduction. The research findings provide recommendations to improve the effectiveness of energy transition policies in Indonesia, while contributing to the achievement of Nationally Determined Contributions (NDC) targets and transformation towards a sustainable energy system. This research is expected to be a practical reference for the government, PT PLN, investors, and international organizations in promoting a more inclusive and integrated energy transition.